Heat transfer efficiency of biomass cookstoves - Zube, Daniel Joseph, author; DeFoort, Morgan W., advisor; Willson, Bryan D., committee member; Maloney, Eric D., committee member (Colorado State University. Libraries, 2010)
Nearly half of the world's human population burns biomass fuel to meet home energy needs for heating and cooking. Biomass combustion often releases harmful chemical compounds, greenhouse gases, and particulate matter into the air which all have a detrimental effect on both human health and global climate and ecology. In order mitigate the harmful effects of biomass combustion, thermal efficiency of the combustion process must be improved. Thermal efficiency is influenced equally by combustion efficiency and heat transfer efficiency, but the emphasis of this research is on heat transfer efficiency since it offers the most room for improvement. A theoretical approach is taken to understand the fundamental physics underpinning the three modes of heat transfer: conduction, convection, and radiation. A strong theoretical understanding of each mode as it applies to cookstoves is established and used as a tool to evaluate potential design enhancements. Based on these evaluations, certain design modifications are suggested as a practical means to boost heat transfer efficiency. Future research topics are suggested which will further increase the accuracy of theoretical predictions surrounding stove performance.
Department Head: Allan Thomson Kirkpatrick.